PENGARUH BRISK WALKING EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PUSKESMAS TANAH TINGGI KOTA BINJAI TAHUN 2023 - Herawati, Leli; Wahyuni, Sri (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Hypertension is defined as persistent blood pressure where the systolic pressure is ? 140 mmHg and the diastolic pressure is ? 90 mmHg. Hypertension not only reduces the quality of life, but can threaten the sufferer's life. The aim of the study was to determine the effect of brisk walking exercise on blood pressure in hypertension sufferers at the Tanah Tinggi Health Center. The type of research used was a quasi experiment with a non-equivalent control group design pretest posttest method. The total population was 346 samples taken using purposive sampling technique, a sample of 34 respondents per group. The researcher's independent variabl in the study provided brisk walking exercise intervention. The researcher's dependent variable is blood pressure. The research was carried out using treatment and control to obtain respondent data. Statistical testing of research data uses the Independent T-Test. The research results obtained before the brisk walking exercise were carried out in the control and treatment groups all had hypertension. Statistical test results using the Independent T- test where systole p value = 0.000 and diastole p value = 0.000 with a value = 0.05. So that the p value is 0.000 <0.05, then Ho is rejected and Ha is accepted, which means there is an effect of brisk walking exercise on reducing blood pressure. The conclusion was that after the brisk walking exercise was carried out, the blood pressure of the respondents decreased.